King Mango Enterprise : "Mango Crisps" / Nur Hanani Masirun...[et.al] - Shafiee, Ain Natasha; Abdul Aziz, Nur Afiqah; Mohamed, Mohamad Nor Hazazy; Rahmat, Muhammad Alif Hafizuddin (Faculty of Plantation and Agrotechnology, 2017)
King Mango Enterprise is a "Halal" food product that produce by Muslim company that mainly focuses on the production of mango crisp in the area of Malacca. This business company was run by a General Manager and another 4 other manager which is Administration, Operation, Marketing, and Financial Manager. Each of this manager have different types of task and play an important role in making this business run well and achieve their target.